Safeguarding against corruption during the pandemic: Recent evidence from the G20 countries - Tanu M. Goyal (Indian Council for Research on International Economic Relations (ICRIER), 2022)
When Covid-19 was declared as a pandemic, countries administered lockdowns and stimulus packages were announced to address the deteriorating situation. For implementing these packages, routine control measures were simplified and often relaxed. The G20 countries were quick to react by administering relief packages and at the same time, the G20 acknowledged that emergency measures, in the times of economic and social fragility, may result in corruption. This paper investigates the potential threats of corruption due to fiscal expansion during the pandemic and discusses recent evidence from G20 members on the mechanisms in place to address corruption. More generally, using available secondary data, the paper compares how the G20 members and non-members have performed on the corruption perception index over the years. The paper found that to address the Covid-19-situation, most G20 countries announced a mix of budget and off-budget items as stimulus packages. Almost all G20 countries reported corruption risks, the most common being corruption and fraud risks in public procurement of medicines, medical supplies or any related goods or services. At the same time, the G20 undertook accountability assessment for its members and the G20 countries formulated mechanisms to address corruption risks, frequenting the use of technology and by enhancing the role of civil society. Both, in comparison to the last year, and over the last decade, the G20 countries have outperformed the non-member countries on corruption perception. Going forward, the papers argues that the G20, as a platform can affectively continue to address corruption risks by building cooperation and sharing best practices, especially in areas where some G20 members can lead by example.
Keywords: F53; F55; N40; D73; D78; 330; Covid-19; fiscal expansion; corruption; global governance; G20; international institutions